Suitability Analysis of Drinking Water from The Springs of Deumai Watershed Ilam, Nepal - Shrestha, Priya Darshan; Khanal, Manoj; Shilwal, Champak Babu (Himalayan Journal of Science and Technology, 2023)
Spring is one of the major sources of drinking water in hilly and Himalayan region. The overall purpose of this study was to analyse the suitability of drinking water by studying the physicochemical properties. Springs of Deumai watershed Ilam, Nepal was investigated for water samples and the physicochemical parameters studied were TDS, pH, temperature, total hardness, alkalinity, total iron and major ion concentrations (Na+, K+, Mg2+, Ca2+, Cl–, SO42–, NO3–) to describe the water’s chemical characteristics. The physical parameters were determined using pH meter, laboratory thermometer etc. The determination of concentration of chemical parameters was performed by using spectrophotometric method, flame photometric method and titration method. The average pH was found 7.47 and average temperature was found to be 19.4ºC. The dominance trend for major cations was Ca2+ > Na+ > Mg2+ > K+ > Fe and for anions was HCO3– > Cl– > NO3– > SO42–. All the values obtain were within the range specified by WHO and NDWQS guidelines of drinking water. According to the findings and comparison with the guidelines of drinking water given by World Health Organization (WHO) and National Drinking Water Quality Standard (NDWQS), the water quality for drinking water was found within the standards set by them.